The Hemoglobin examination to improvement awareness blood donation on cadres at rw 05 Patangpuluhan, Wirobrajan, Yogyakarta - Yuli Astuti; Tri Djoko Endro Susilo; Nanda Achmad Syafei; Siti Munifa Tongkasi (Universitas Ahmad Dahlan, 2023)
Background Blood service technicians must ensure that the blood to be used for the transfusion process is safe and quality blood. Hemoglobin examination is most of important to blood donation selection. Who will be to take blood donation its must to have hemglobin level is normal. That condition will be impact to quality of blood product. Objectif of this community service is to examination hemoglobin on cadres at RW 05 Patangpuluhan, Wirobrajan, Yogyakarta to improvement awarenes blood donation. Method of this community services is: the preparation and the implementation stage. The prapration stages include obtaining permits, preliminary studies with field observations, collecting materials and preparing tools and materials during activities and coordinating with cadres. Implementation stage are to check hemoglobin on cadres in Patangpuluhan Village. Result of this community service were 23 cadres who participated in the service activities. The results obtained were hemoglobin are Normal (34.79%), anemia (47.82%), polistemiavera (4.34%), refusel to examination (13.5%). Conclusions of 23 participants who hemoglobin examination mostly within normal limits.